2016
DOI: 10.1007/s11121-016-0657-0
|View full text |Cite
|
Sign up to set email alerts
|

Parenting in 2 Worlds: Effects of a Culturally Adapted Intervention for Urban American Indians on Parenting Skills and Family Functioning

Abstract: Parenting in 2 Worlds (P2W) is a culturally grounded parenting intervention that addresses the distinctive social and cultural worlds of urban American Indian (AI) families. P2W was culturally adapted through community-based participatory research in three urban AI communities with diverse tribal backgrounds. This paper reports the immediate outcomes of P2W in a randomized controlled trial, utilizing data from 575 parents of AI children (ages 10–17). Parents were assigned to P2W or to the comparison group, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…Eight programs discussed changes to the delivery methods of the original program in order to address cultural differences (Table 3). These types of changes included re‐organizing sessions into weekly 2‐hour lunchtime sessions over 5 weeks rather than weekly 1‐hour lunchtime sessions over 8 weeks (Bogart et al., 2013), adapting workshop lessons to introduce and approach topics holistically and experientially rather than presenting material as a set of elements or steps to be assembled into a whole (Kulis et al., 2016), and replacing the use of puppets, which require the children to be comfortable taking risks and performing in front of peers, with role plays modeled by facilitators (Marek, Brock, & Sullivan, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Eight programs discussed changes to the delivery methods of the original program in order to address cultural differences (Table 3). These types of changes included re‐organizing sessions into weekly 2‐hour lunchtime sessions over 5 weeks rather than weekly 1‐hour lunchtime sessions over 8 weeks (Bogart et al., 2013), adapting workshop lessons to introduce and approach topics holistically and experientially rather than presenting material as a set of elements or steps to be assembled into a whole (Kulis et al., 2016), and replacing the use of puppets, which require the children to be comfortable taking risks and performing in front of peers, with role plays modeled by facilitators (Marek, Brock, & Sullivan, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…14 Others found that AI parents can be more responsible for providing support and encouragement, while extended families assume the role of discipline, such as communicating dangers of substance use. 38 We asked specifically about parent communication, which may have obscured effects due to extended family communications.…”
Section: Discussion Of Study Findingsmentioning
confidence: 99%
“…There is, of course, much diversity in family life across the AI/AN population. For example, AI/AN families living on reservations are more likely to rely on extended family (e.g., multiple generations living in one household) [11], or other tribal relations [12]) for practical purposes (e.g., economic support, caregiving) and moral/spiritual guidance [13]. On reservations, the extended family also plays a role in reinforcing cultural beliefs and values [14].…”
Section: Unique Aspects Of Ai/an Familiesmentioning
confidence: 99%